Respuesta :

2x + 3= -4
 take the three away and  take it away from the -4 ( you do this to get rid off the the =3 , what you do to one side you have to do to the other side )
2x = -7
 now divide -7 by 2 to get the value of x
-7/2 = -3.5
 so x= -3.5

as for the other equation :
now you need to substitute x = -3.5 into 5x + 2y = 1 to find y .
so you should have (5 x -3.5 ) + 2y =1 .
Calculate what's in the brackets  ,  you should have -17.5 + 2y = 1

Now to get rid of the -17.5 add 17.5 to both sides of the = sign, you should now have 2y = 18.5 .

divide both sides by 2 to find the value of y , so you should have y = 9.25 .

To make sure you have the correct values , substitute both values into 5x+2y to see whether the answer will be 1 . (If it is , your values are correct , if not then go back over what you did and see whether you followed the steps correctly .)

(5x-3.5) + (2x 9.25 )
= -17.5 + 18.5
=1 

I hope that was helpful ! 
Good luck :)
ACCESS MORE